The Effect of Capital Expenditure, Labor,and Human Development Index Gross Regional Domestic Product Per Capita In East Java Province from 2013 to 2023 - Sugiarti Sugiarti; Muhammad Nurul Khusyaini; Muhammad Bintang Wijaya; Hanifah Mumtaz Al Rosyidah; Amanda Lidia Sari; Tsabita Sabrina; Zainal Abidin (Buletin Ekonomika Pembangunan, 2026)
This study aims to analyze the effect of capital expenditure, infrastructure and the Human Development Index (HDI) on Gross Regional Domestic Product (GRDP) in East Java Province. Using secondary data obtained from the Central Statistics Agency (BPS) and related agencies during the period 2013_2023, the analysis was conducted using the Panel Data regression method The results show that capital expenditure has a significant positive effect on GRDP, indicating that labor contributes to economic growth. In addition, good labor is also proven to contribute positively to GRDP, while HDI shows a significant effect, reflecting the importance of human resource qualityin driving economic growth. This study recommends increasing capital expenditure and labor as the main strategies in driving economic growth in East Java Province Keyword: Economic Growth, Gross Domestic Product, Capital Expenditure, Human Development Index, Labor.